2018
DOI: 10.1111/jcpp.12986
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic experiences are associated with health anxiety and functional somatic symptoms in preadolescence

Abstract: Background Health anxiety (HA) is an increasing public health problem related to increased health service costs, and associated with functional somatic symptoms (FSS) and considerable personal suffering. Abnormal bodily experiences which may resemble HA and FSS are common in psychotic disorders, but a potential link between HA and psychosis vulnerability in childhood is largely unexplored. The current study estimates the association between subclinical psychotic experiences (PE) and HA and FSS in a general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…The Strengths and Difficulties Questionnaire (SDQ) total scale is a commonly used general psychopathology measure (see, e.g. Rimvall et al., ). While it includes a subscale of peer problems, which is one aspect of social difficulties, the SDQ total does not include autistic traits per se.…”
Section: It Is Not Yet Clear How Neurodevelopmental Conditions Are Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The Strengths and Difficulties Questionnaire (SDQ) total scale is a commonly used general psychopathology measure (see, e.g. Rimvall et al., ). While it includes a subscale of peer problems, which is one aspect of social difficulties, the SDQ total does not include autistic traits per se.…”
Section: It Is Not Yet Clear How Neurodevelopmental Conditions Are Inmentioning
confidence: 99%
“…Also in this issue, Rimvall et al. explore novel questions about how positive psychotic experiences such as hallucinations and delusions are associated with health anxiety and functional somatic symptoms (Rimvall et al., ). In their cohort of 11‐ to 12‐year‐olds, they find significant cross‐sectional associations.…”
Section: The P Factor As An Essential Covariate In Studies Of Specifimentioning
confidence: 99%
“…Together with the current findings and retrospective reports suggesting that adult HA is often preceded by similar symptoms in childhood and adolescence (Noyes et al, 2002), the overall evidence suggests continuity of HA across the life span. As outlined in the introduction, important findings from cross-sectional studies on children and adolescents have shown that HA is associated with a broad array of other types of psychopathology (Oliver et al, 2018;Rask et al, 2016;Rimvall et al, 2019;Sirri et al, 2015;Wright et al, 2016). Crucially, even in the adjusted analyses, there was still evidence of an independent effect of high HA at age 11 on the risk of high HA at age 16, since the findings were only partially explained by chronic somatic illness.…”
Section: Discussionmentioning
confidence: 96%
“…For the analyses on HA continuity from age 11 to age 16 years, HA symptoms at both ages were dichotomized into high (top 10%) and low (bottom 90%) scores based on the entire population participating at the respective follow-ups, thus including individuals for whom longitudinal data were not available. This approach was in line with previous studies of the CCC2000 11-year follow-up (Rask et al, 2016;Rimvall et al, 2019). We categorized HA symptoms from age 11 to 16 into four groups based on continuity of symptoms: a) persistent (high score at both follow-ups), remitting (high at age 11, low at age 16), incident (low at age 11, high at age 16) and consistently low HA (low at both follow-ups).…”
Section: Statistical Analysesmentioning
confidence: 87%
See 1 more Smart Citation